2011
DOI: 10.1111/j.1440-0960.2010.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomatoid papulosis in children: Experience of five cases and the treatment efficacy of methotrexate

Abstract: We present a case series of childhood lymphomatoid papulosis (LyP), an entity which is commonly misdiagnosed and poorly described in the paediatric dermatology literature. Clinically and histologically, the features of LyP in children can mimic insect bite reactions, with prominent dermal neutrophils and eosinophils. However, CD30 immunohistochemical staining of atypical lymphocytes within a mixed inflammatory infiltrate should point to the diagnosis of LyP. There is no consensus to guide management of childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…MTX has been used for treating lymphomatoid papulosis, pityriasis lichenoides and palmoplantar pompholyx, but evidence for its efficacy is limited to case reports. Other possible indications supported by case reports include oral lichen planus, dermatomyositis, cutaneous vasculitis (including cutaneous polyarteritis nodosa, Behçet disease and erythema elevatum diutinum), pyoderma gangrenosum, necrobiosis lipoidica, granuloma annulare, alopecia areata, chronic idiopathic urticaria, Hailey‐Hailey disease and Langerhans cell histiocytosis …”
Section: Indicationsmentioning
confidence: 99%
“…MTX has been used for treating lymphomatoid papulosis, pityriasis lichenoides and palmoplantar pompholyx, but evidence for its efficacy is limited to case reports. Other possible indications supported by case reports include oral lichen planus, dermatomyositis, cutaneous vasculitis (including cutaneous polyarteritis nodosa, Behçet disease and erythema elevatum diutinum), pyoderma gangrenosum, necrobiosis lipoidica, granuloma annulare, alopecia areata, chronic idiopathic urticaria, Hailey‐Hailey disease and Langerhans cell histiocytosis …”
Section: Indicationsmentioning
confidence: 99%
“…The reports of children affected by LyP were mostly of the three-first types A to C which may be explained by the fact that LyP type D and E have been described only very recently. 62,[64][65][66] In our series of LyP biopsies in children comprised the histological types A, C and E with the latter found in two of our patients. Due to the presence of eosinophils in paediatric LyP and common pruritus, bite reaction is also a differential diagnostic consideration.…”
Section: Cutaneous T-cell Lymphomasmentioning
confidence: 96%
“…Also Yip et al [4] have reported MTX to be a safe and effective treatment for LyP in children. In a series of nine cases of granulomatous and eccrinotropic LyP by Crowson et al three patients received MTX: first patient showed complete resolution of lesions without recurrence; no response was seen in second patient; and, third patient was just started on MTX with no resolution of lesions yet.…”
Section: B Amentioning
confidence: 99%
“…In adult-onset LyP, low-dose MTX between 10-25 mg weekly is recommended as the treatment of choice for aggressive or refractory disease. [3,4] The overall prognosis for LyP is good and the disease follows a benign course, though clonal T cell gene rearrangements can be demonstrated in 70% cases. LyP may be preceded by, associated with, or followed by another cutaneous lymphoma like Hodgkin's disease, cutaneous T cell lymphoma or anaplastic large cell lymphoma (ALCL).…”
Section: B Amentioning
confidence: 99%